Examining the Sustainability of Food Consumption Based on Religiosity Dimensions in Urban and Sub-Urban Communities - Habibi, Ahmad; Hanif, Hanif; Normasyhuri, Khavid (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality:  This study offers a new perspective on the relationship between religiosity and sustainable food consumption in urban and peri-urban communities in Lampung, Indonesia. Research Objectives: The objective was to examine the differences in sustainable food consumption between urban and peri-urban communities, exploring the role of religious beliefs in shaping consumption behavior.Research Methods: A quantitative approach using comparative analysis was used. Data were collected from 250 respondents using purposive sampling, analyzed through statistical tools such as the Shapiro-Wilk Normality Test and Independent Sample t-test.Empirical Results: This study found that there were no differences in consumption behavior between urban and suburban communities with the dimensions of religiosity in the aspects of beliefs and practices. There were differences in consumption behavior between urban and suburban communities with the dimensions of religiosity in the aspects of knowledge and behavior.Implications: This study highlights the need for policymakers and businesses to consider religious factors in promoting sustainable consumption, suggesting that urbanization and access to religious education influence food choices based on religiosity.JEL Classification: D12, D19